2003
DOI: 10.1242/jeb.00107
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific expression of inducible and constitutive Hsp70 isoforms in the western painted turtle

Abstract: Expression of Hsp73 and Hsp72 in four tissues of the naturally anoxia-tolerant western painted turtle (Chrysemys picta) was investigated in response to a 24 h forced dive and following 1 h recovery. Of the tissues examined, brain and liver displayed approximately threefold and sevenfold higher basal Hsp73 expression than heart and skeletal muscle. Basal Hsp72 expression was relatively low in all tissues examined. After the 24 h forced dive and 1 h recovery, Hsp73 expression did not differ significantly from ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
4
19
3
Order By: Relevance
“…Antibodies to Hsp72 and Hsc73 used for this study were previously reported to react specifically with turtle isoforms detecting in each case a single discrete spot by twodimensional gel electrophoresis (Scott et al, 2003). Hsp72 was readily detected in normoxic brain, indicating a high level of baseline expression (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Antibodies to Hsp72 and Hsc73 used for this study were previously reported to react specifically with turtle isoforms detecting in each case a single discrete spot by twodimensional gel electrophoresis (Scott et al, 2003). Hsp72 was readily detected in normoxic brain, indicating a high level of baseline expression (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…However, the current study examined changes in progressive anoxia up to 12 hours, whereas Scott et al (2003) measured changes after 24 hours of forced submergence. Forced submergence might also be an additional stress for the HSP system.…”
Section: Discussionmentioning
confidence: 99%
“…and HSP70 induction levels in response to toxins are in agreement with previous reports Scott et al 2003 and). …”
Section: Estimation Of Specific Stress Proteins Using Elisasupporting
confidence: 93%
“…Chang et al (2000) provided the first evidence of increased Hsp70 expression in painted turtle myocardium subjected to a 12·h forced dive, but the antibody they used did not distinguish between the constitutive (Hsp73) and inducible (Hsp72) isoform. More recently, Scott et al (2003) reported an increase in the expression of Hsp72 but not Hsp73 in brain, heart and skeletal muscle of western painted turtles force-dived for 24·h at 17°C.…”
mentioning
confidence: 99%
“…Since this species undergoes 'translational arrest' during anoxia (Jackson, 2000), the specific upregulation of stress proteins in dived turtles suggests a protective role in long-term anoxic survival (Chang et al, 2000;Scott et al, 2003). However, it is not known whether turtle tissues induce Hsp expression early in a dive period or upregulation of Hsp expression occurs late in a dive as a part of a rescue mechanism triggered near the limit of survival.…”
mentioning
confidence: 99%